a Analysis of the Effect of Motivation, Work Stress and Workload on the Performance of Health Workers During the Covid 19 Pandemic at the Pelaihari Community Health Center, Tanah Laut Regency - Nunung Maryanti; Zainal Arifin; Ibrahim Daud (Health Media, 2022)
This study aims to determine whether motivation, work stress, and workload partially or simultaneously affect the performance of health workers during the Covid-19 pandemic at the Pelaihari Health Center, Tanah Laut Regency.The research method is an explanatory research. The population in this study were all health workers at the Pelaihari Health Center, which amounted to 79 people. The sampling technique in this study used a saturated sampling technique or census sampling, where all members of the population were sampled. The analytical technique used is multiple linear regression analysis with SPSS 25.0 for windows program.The results showed that partially motivation had no significant effect on the performance of health workers during the Covid-19 pandemic at the Pelaihari Health Center, Tanah Laut Regency. Work stress has a significant effect on the performance of health workers during the Covid-19 pandemic at the Pelaihari Health Center, Tanah Laut Regency. The workload has a significant effect on the performance of health workers during the Covid-19 pandemic at the Pelaihari Health Center, Tanah Laut Regency. Meanwhile, simultaneously motivation, work stress, and workload have a significant effect on the performance of health workers during the Covid-19 pandemic at the Pelaihari Health Center, Tanah Laut Regency.